Characterization of Perfluorooctylbromide-Based Nanoemulsion Particles Using Atomistic Molecular Dynamics Simulations - Lee, Sun-Joo (2010)
Perfluorocarbon-based nanoemulsion particles have arisen as promising platforms for the cellular delivery of imaging and therapeutic agents to specific targets. However, current knowledge of the agent delivery mechanism is limited to qualitative and phenomenological models. Lack of detail at the molecular level has hence delayed optimizing or customizing nanoemulsion particles for therapeutic and imaging applications. Here we report the first atomistic structural details of a perfluorooctylbromide-based (PFOB-based) nanoemulsion particle (NEP) with a 1-palmitoyl-2-oleoyl-phosphatidylcholine (POPC) lipid emulsifier. Newly developed PFOB force field parameters were used in molecular dynamics simulations to model the PFOB-NEP interface in a planar configuration. These PFOB force field parameters were developed and tested to reproduce the characteristics of bulk PFOB as well as PFOB at interfaces with water and emulsifying phospholipids. The modeled PFOB-NEP interface demonstrated significant intercalation of PFOB into the emulsifying lipid mono-layer and consequent changes in the structural, electrostatic, and mechanical properties of the POPC monolayer and PFOB. This intercalation provides an explanation for experimental data demonstrating melittin tryptophan fluorescence quenching upon binding to the nanoemulsion particles through the observation of direct contact between the melittin tryptophan and the PFOB bromine. Additionally, the atomistic details of the PFOB-NEP interface structure provided by our simulations are used to suggest the influence of each component on PFOB-NEP delivery function which will be tested in future coarse-grained simulations.